2016
DOI: 10.5430/jnep.v6n5p91
|View full text |Cite
|
Sign up to set email alerts
|

Conflict resolution strategies of nurses in a selected government tertiary hospital in the Kingdom of Saudi Arabia

Abstract: Background: Conflict is inevitable and can be found in all settings. It can co-exist between and among health care professionals such as doctors and nurses and their patients. The roles of the nurses in each scenario and the kind of strategies they utilized also vary. This study aimed to determine the conflict resolution strategies of nurses in a selected government tertiary hospital in the Kingdom of Saudi Arabia. Methods: Utilizing a Descriptive Correlational Research Design, 78 nurses were asked to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 19 publications
4
37
3
2
Order By: Relevance
“…Similar to other hospitals, the existence of intra-group conflict involving members of two professions that closely collaborate to deliver patient care is evident in these three hospitals [3,30,33,34,38]. Other antecedents to conflict present in these three hospitals include the fact that their medical and nursing personnel are diversely distributed in terms of gender [50,51,52], age [53] and years of experience [12,37,50].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similar to other hospitals, the existence of intra-group conflict involving members of two professions that closely collaborate to deliver patient care is evident in these three hospitals [3,30,33,34,38]. Other antecedents to conflict present in these three hospitals include the fact that their medical and nursing personnel are diversely distributed in terms of gender [50,51,52], age [53] and years of experience [12,37,50].…”
Section: Discussionmentioning
confidence: 96%
“…With respect to conflict among nurses and physicians, the conflict resolution strategies of avoidance and compromise are commonly used to remedy conflict on an interim basis [2]. A study conducted among 78 nurse respondents in a selected tertiary hospital in the Kingdom of Saudi Arabia revealed that they most often utilized competing in conflict situations with physicians while accommodating was the least used conflict resolution strategy with doctors [38]. Among nurse managers and staff nurses at Menoufiya University Hospital and Shebin El-Kom Teaching Hospital in Egypt, avoiding and competing were the most and least utilized conflict management style by the respondents, respectively [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A competing style has been reported to be ineffective as it causes intimidation and interferes with communication, discussion of alternative ideas and attempts at problem solving. In fact, competing style was found to be the least used strategy by nurses in a study by Baddar, Salem and Villagracia (2016:96).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…It has been reported that when conflicts between nurses are not effectively managed, they impair interpersonal and professional relationships in the long term, affect the functioning of an organisation negatively, and increase the cost of patient care. It also causes emotional exhaustion, depersonalization, and a decrease in job satisfaction in health team members (Baddari et al., ; Brinkert, ; Tilden, ; Yılmaz & Öztürk, ). When conflicts and/or administrative problems are encountered at different levels of nursing services, nurse managers’ communication skills and approaches play a key role in problem solving (Brinkert, ; Yılmaz & Öztürk, ).…”
Section: Literature Reviewmentioning
confidence: 99%